Electoral Realignments within the Left in the Aftermath of Neoliberal Crises. A Critical Juncture Framework for Latin America and Southern Europe - Padoan, Enrico (PARTECIPAZIONE E CONFLITTO, 2021)
The Latin American "Turn to the Left" consisted in either the consolidation of traditional left-of-centre parties or the emergence of new anti-neoliberal populist projects that decisively shaped the respective national party systems in reaction to major neoliberal crises. Some Southern European countries similarly experienced the rise of new populist parties (Podemos, Syriza and the Five Star Movement) while in Portugal we witnessed the consolidation of the existing left-of-centre parties. This article proposes a middle-range theory to give a cross-regional account of the eventual emergence of different anti-neoliberal populist parties in the aftermath of a neoliberal economic crisis. The argument focuses on the heterogeneity of such an 'Anti-Neoliberal Populism' category, by looking at the party organisation and the relationship with the unions and with the anti-austerity social movements. The framework thus proposes four different categories of "successful political projects" emerged in the aftermath of the crisis: a "Labour-based Left" (in Uruguay and Portugal); a "party-rooted populism" (in Argentina and Greece); a "movement (based) populism" (in Bolivia and Spain); and a "leader-initiated populism" (in Venezuela and Italy).